2021
DOI: 10.1038/s41598-021-84306-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced gonadotroph stimulation by ethanolamine plasmalogens in old bovine brains

Abstract: Ethanolamine plasmalogens (EPls), unique alkenylacyl-glycerophospholipids, are the only known ligands of G-protein-coupled receptor 61—a novel receptor co-localised with gonadotropin-releasing hormone receptors on anterior pituitary gonadotrophs. Brain EPl decreases with age. Commercial EPl—extracted from the cattle brain (unidentified age)—can independently stimulate FSH secretion from gonadotrophs. We hypothesised that there exists an age-related difference in the quality, quantity, and ability of bovine bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Another important reason is that important synthesis enzymes, such as GNPAT, AGPS, and FAR1, are expressed in the preoptic area, arcuate nucleus, and median eminence including the secretory zone (Kadokawa et al, 2021;Figure S1). Whale brain EPls stimulated LH and FSH secretion from bovine AP cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another important reason is that important synthesis enzymes, such as GNPAT, AGPS, and FAR1, are expressed in the preoptic area, arcuate nucleus, and median eminence including the secretory zone (Kadokawa et al, 2021;Figure S1). Whale brain EPls stimulated LH and FSH secretion from bovine AP cells.…”
Section: Discussionmentioning
confidence: 99%
“…We used cultured bovine AP cell models as described in previous studies to evaluate the effects of various hormones, including insulinlike growth factor I, kisspeptin, estrogens, anti-Müllerian hormone, and EPl (Ezzat et al, 2010;Hashizume et al, 2002;Kadokawa et al, 2021Kereilwe, Pandey, Borromeo, & Kadokawa, 2018;Otsuka & Kadokawa, 2017).…”
Section: Ap Cell Collection and Culture And Analysis Of The Effects O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike human AP glands, bovine AP glands can be obtained for primary culture as they can be collected from slaughterhouses. Indeed, using bovine gonadotrophs, we discovered new receptors that control LH and FSH secretion, colocalizing with gonadotropin-releasing hormone (GnRH) receptor (GnRHR) in the lipid rafts of bovine gonadotrophs [ 7 , 11 , 12 , 13 ]. Bovine ACE2 contains most of the key residues for the receptor-binding domain of SARS-CoV-2 [ 14 ] (details are shown in Supplementary Fig.1 ), and SARS-CoV-2 replicates in bovine respiratory tissues [ 15 ].…”
mentioning
confidence: 99%
“…In addition, we have also found that Pls have neuroprotective effects and can induce cellular signaling such as ERK and Akt via the G proteincoupled receptors (GPCRs), including GPCR21 (912). Growing evidence suggests that these special lipids could function as ligands that activate the GPCRs to elicit a biological function (13,14). Therefore, if NK cells express these GPCRs, it could be possible that Pls might activate these GPCRs to regulate NK cell functions.…”
mentioning
confidence: 99%